Legal Analysis of Granting Mining Business Licenses to Community Organizations (Ormas) - Astinda, Afifuddin Nur Rosyid; Haidar, Muhammad Bagas; Pratama, Wahyu Pujo (Faculty of Law, Musamus University, 2024)
The government, through the Minister of Investment, has decided that religious organizations (ormas) are allowed to manage mines. This decision is stipulated in Peraturan Pemerintah (PP) Nomor 25 Tahun 2024 concerning Amendments to Peraturan Pemerintah Nomor 96 Tahun 2021 on the Implementation of Mineral and Coal Mining Business Activities. This policy was made as the government's effort to achieve economic justice and encourage the economic independence of ormas, enabling them to support their programs in education, social, religious, and cultural fields. In Law Number 3 of 2020, religious organizations were not specifically mentioned as entities that can be authorized to manage mining. In that law, the entities eligible for such authority are state-owned enterprises (BUMN), regional-owned enterprises (BUMD), cooperatives, and private companies. This study aims to analyze the legal aspects of granting mining business licenses (IUP) to religious mass organizations and to assess the feasibility of such organizations if the government grants them permission to manage mines. The study found that there are differences between Undang-Undang No. 3 Tahun 2020 on the Implementation of Mining Activities and PP No. 25 Tahun 2024. Additionally, from an economic perspective, religious organizations are not yet considered eligible to receive IUP because their main orientation is to promote freedom of speech and association, which contrasts with business objectives that prioritize profit and financial gain.